2021
DOI: 10.36941/ajis-2021-0056
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Nuances in Work Attitudes and Behaviors: Towards a Model of African Work Culture

Abstract: This study explored managers’ perception of the work behaviors and attitudes of Nigerian workers with reference to Nigeria’s cultural orientation and the global culture. It compared Japan, USA and Nigeria on Hofstede’s cultural dimensions, work culture and organizational outcomes. Descriptive survey design and purposive sampling technique were used in data collection. A total of 131 managers (74 males and 57 females) from manufacturing organizations in Ota, Ogun State were interviewed. The structured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Uncertainty avoidance reflects the extent to which people in a society try to avoid situations that do not provide certainty; the masculinity-femininity dimension reflects how societies distribute roles based on gender; the individualism-collectivism dimension describes the extent to which individuals in a society are either integrated into groups or encouraged to be independent; long-term orientation refers to the extent to which a community or society embrace long-term and futuristic commitments, as opposed to commitments that are shortterm focused, thereby differentiating societies that are able to embrace change more rapidly than the others. Although Hofstede's framework has been challenged for various reasons, including the validity and representativeness of his data (Baskerville, 2003;Javidan, House, Dorfman, Hanges, & De Luque, 2006;, his work continues to be referenced to this day (Areiqata et al, 2021;Gallego-Álvarez & Pucheta-Martínez, 2021;Kaasa, 2021;Olatunji, Makhosazana, & Vezi-Magigaba, 2021;Olowookere, Agoha, Omonijo, Odukoya, & Elegbeleye, 2021). The various disciplines that reference his work include cross-cultural management (Beugelsdijk, Kostova, Kunst, Spadafora, & Van Essen, 2018;Klasing, 2013), country-level culture (Beugelsdijk, Kostova, & Roth, 2017) and international business (Kirkman, Lowe, & Gibson, 2006).…”
Section: Hofstede Cultural Framework and The Globe Cultural Dimensionsmentioning
confidence: 99%
“…Uncertainty avoidance reflects the extent to which people in a society try to avoid situations that do not provide certainty; the masculinity-femininity dimension reflects how societies distribute roles based on gender; the individualism-collectivism dimension describes the extent to which individuals in a society are either integrated into groups or encouraged to be independent; long-term orientation refers to the extent to which a community or society embrace long-term and futuristic commitments, as opposed to commitments that are shortterm focused, thereby differentiating societies that are able to embrace change more rapidly than the others. Although Hofstede's framework has been challenged for various reasons, including the validity and representativeness of his data (Baskerville, 2003;Javidan, House, Dorfman, Hanges, & De Luque, 2006;, his work continues to be referenced to this day (Areiqata et al, 2021;Gallego-Álvarez & Pucheta-Martínez, 2021;Kaasa, 2021;Olatunji, Makhosazana, & Vezi-Magigaba, 2021;Olowookere, Agoha, Omonijo, Odukoya, & Elegbeleye, 2021). The various disciplines that reference his work include cross-cultural management (Beugelsdijk, Kostova, Kunst, Spadafora, & Van Essen, 2018;Klasing, 2013), country-level culture (Beugelsdijk, Kostova, & Roth, 2017) and international business (Kirkman, Lowe, & Gibson, 2006).…”
Section: Hofstede Cultural Framework and The Globe Cultural Dimensionsmentioning
confidence: 99%
“…However, it is crucial to do empirical research to identify a suitable leadership style to address the issue of deviant behaviours among academics, given the worrisome rise in misbehaviour among Nigerian academics (Adeoti et al, 2021). Coincidentally, according to a recent study, Nigerian workers are primarily motivated by reward and punishment (Olowookere et al, 2021), hence, contingent reward leadership behaviour seems to be an appropriate concept to study in the Nigerian context. This finding, therefore, adds TL as one important antecedent of WD.…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…(Amin et al, 2018a;Erinosho et al, 2021;Olufemi, 2020), is an indication that something is fundamentally wrong with the leadership style and employee orientation in that context (Hendricks & Louw-Potgieter, 2012;Zheng et al, 2020). We draw from the literature's seeming negligible attention to the leadership-WD relationship in Nigeria, and the recent research findings that suggest that positive stimulus (reward) and negative reinforcement (punishment) have a significant relationship with employee behaviour in Nigeria (Olowookere et al, 2021), to investigate the impact of leader reward and punishment behaviour known as transactional leadership (Bass & Bass) on the WD. Furthermore, previous studies linking employee misbehaviour with leadership style (Amin et al, 2018a;Zheng et al, 2020) have typically failed to look into the interaction of other variables, such as employee commitment and his first experiences in the workplace.…”
Section: Introductionmentioning
confidence: 97%
“…Scholars stress that the smaller the national cultural distance, the more comfortable the transfer of HRM practices from home companies to foreign subsidiaries. National cultural distance has been widely analysed in IHRM literature (Ayentimi et al 2018a;Olowookere et al 2021). Therefore, it is challenging to transfer some HRM practices between countries with varied national cultures (Al-Sarayrah et al 2016;Ogunsegha, 2013;Thomas & Peterson, 2017;Zhou et al 2020).…”
Section: Cultural Approachmentioning
confidence: 99%
“…Accordingly, an organisation can also take the place of a family by providing purpose, security and identity. Olowookere et al (2021) suggested that individualism was associated with a lack of generosity and caring. Individuals are seen as alienated from their culture, traditions, and each other in the Sub-Saharan African context.…”
Section: Socio-cultural Elementsmentioning
confidence: 99%